2019
DOI: 10.1021/acs.jpca.8b09306
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ammonia and Water on the Fate of Sulfur Trioxide in the Troposphere: Theoretical Investigation of Sulfamic Acid and Sulfuric Acid Formation Pathways

Abstract: Reaction of ammonia with SO3 as a potential source of sulfamic acid in the troposphere has been investigated by means of electronic structure and chemical kinetic calculations. Besides, the hydrolysis reaction, which is known to be a major atmospheric decay channel of SO3, has also been investigated. The catalytic effects of ammonia and water on both the reactions have been studied. Rate coefficients for all the studied reaction channels were calculated using the transition state theory employing pre-equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 64 publications
2
35
1
Order By: Relevance
“…Assuming that the intermediate IM was in equilibrium with the corresponding reactants (HO 2 and HO 2 ··· X ) and was at steady state, [ 52 ] the high‐pressure limit rate constant k b between HO 2 ··· X and HO 2 has been performed as Equation (). This method has been used in many atmospheric reactions [ 53–58 ] catalyzed by catalyst X , and the predicted rate constants are reasonably consistent with the corresponding experimental values. kb=Keqkuni …”
Section: Methodssupporting
confidence: 69%
“…Assuming that the intermediate IM was in equilibrium with the corresponding reactants (HO 2 and HO 2 ··· X ) and was at steady state, [ 52 ] the high‐pressure limit rate constant k b between HO 2 ··· X and HO 2 has been performed as Equation (). This method has been used in many atmospheric reactions [ 53–58 ] catalyzed by catalyst X , and the predicted rate constants are reasonably consistent with the corresponding experimental values. kb=Keqkuni …”
Section: Methodssupporting
confidence: 69%
“…Thus, H 2 O 2 /HO complex can be neglected and it is not taken into account here. Such investigations have been studied in similar investigations, 52,[66][67][68][69][70] where the dimer between the two reactants has not been involved in X assisted reactions. Above step is followed since it is very necessary to rst identify the stable binary complexes of H 2 O 2 /X and HO/X.…”
Section: Reactantsmentioning
confidence: 99%
“…where K eq1a , K eq1d , and K eq1f respectively denote the equilibrium constant for the formation of H 55,64,65,70,75 The relative rates for v R_AM1 /v R_WM and v R_FA1 /v R_WM within the temperature range of 280-320 K are given in Table 3. As seen in Table 3, when the concentrations of H 2 O at 100% (2.60 Â 10 17 molecule per cm 3 to 2.30 Â 10 18 molecule per cm 3 ) 76 RH and NH 3 at 10 ppbv (2.60 Â 10 11 molecule per cm 3 to 2.30 Â 10 11 molecule per cm 3 ), [22][23][24] the calculated v R_AM1 /v R_WM value is below 2.47 Â 10 À3 to 9.40 Â 10 À5 within the temperature range…”
Section: Relative Impact Of Nh 3 and Hcooh In Tropospherementioning
confidence: 99%
“…The SO 3 • H 2 O complex can form readily, however early investigations of the hydrolysis of SO 3 to form H 2 SO 4 found the uncatalysed rate to be too low to explain the concentration of atmospheric H 2 SO 4 (Wang et al, 1988;Hofmann & Von Ragué Schleyer, 1994;Loerting & Liedl, 2000). Further studies revealed that the formation of H 2 SO 4 is catalysed by collisions with other atmospheric molecules (Akhmatskaya et al, 1997;Hazra & Sinha, 2011;Long et al, 2012;Torrent-Sucarrat, Francisco & Anglada, 2012;Bandyopadhyay, Kumar & Biswas, 2017;Sarkar, Oram & Bandyopadhyay, 2019), where the common denominator is the facilitation of a double proton transfer via the catalysing molecule (Kumar, Sinha & Francisco, 2016). The relative importance of collisions with different molecules is determined by both the atmospheric concentration of the colliding molecule and the species-dependent reaction rate.…”
Section: Introductionmentioning
confidence: 99%